'I wanted to see if you are one of us': The role of identity in the migration experience, a case study of Latin Americans in Australia. Issue 1 (1st March 2020) - Gomes, Catherine; Mejía, Glenda
The literature on transnational migrations tells us that new migrants often look for points of similarity and familiarity with people in destination countries. Whether they intend to settle permanently or if they are transient and temporary, new migrants whatever their histories (e.g., as forced, lifestyle, economic, worker and study migrants) look to create connections with people in destination countries. These connections allow migrants to feel a sense of belonging through established or new community networks that anchor them in their adopted/host country. Moreover, these connections provide practical benefit in terms of allowing migrants to access sources of support (e.g., emotional) and information that are useful in navigating everyday life in the new country. Often, the connections that migrants make are with fellow migrants who are from the same country of origin or migrants from elsewhere primarily because of their shared migration experience. This shared migration experience though is subject to variables such as socio-economic class, education levels, religious affiliation and gender, or a combination of these, just to name a few. For migrants, connecting with people who they identify and recognize as fellow migrant actors, in other words, is a common, if not, instinctual occurrence for migrant belonging-making. While this article acknowledges the significance of the identity-migrant nexus by referring to two separate research projects conducted in Australia involving Latin American participants as a case study, it observes that migrants may also seek out those who they perceive to be fellow co-national/co-ethnic migrants through conventional or perceived visual and cultural markers.